2022
DOI: 10.3390/ijms232315294
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Alpha-Synuclein Inclusions within the Nucleus Predict Impending Neuronal Cell Death in a Mouse Model of Parkinsonism

Abstract: Alpha-synuclein (aSyn) is a 14 kD protein encoded by the SNCA gene that is expressed in vertebrates and normally localizes to presynaptic terminals and the nucleus. aSyn forms pathological intracellular aggregates that typify a group of important neurodegenerative diseases called synucleinopathies. Previous work in human tissue and model systems indicates that some of these aggregates can be intranuclear, but the significance of aSyn aggregation within the nucleus is not clear. We used a mouse model that devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Several studies have reported that the presence of αSyn in the nucleus of cells may underlie αSyn-derived neurodegeneration [6][7][8][9]. We demonstrated that the nucleus-localized αSyn promoted similar cytotoxicity as described in previous studies [7][8][9], and was related to the abnormal rRNA processing and elevated ribosomal protein in this study (Figure 8). Thus, the neurotoxicity of nuclear αSyn might be mediated via ribosomal biogenesis, and the accumulated cytosolic αSyn would propagate the spread of alpha-synucleinopathy and neuroinflammation by the disruption of autophagy-lysosomal degradation pathway.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have reported that the presence of αSyn in the nucleus of cells may underlie αSyn-derived neurodegeneration [6][7][8][9]. We demonstrated that the nucleus-localized αSyn promoted similar cytotoxicity as described in previous studies [7][8][9], and was related to the abnormal rRNA processing and elevated ribosomal protein in this study (Figure 8). Thus, the neurotoxicity of nuclear αSyn might be mediated via ribosomal biogenesis, and the accumulated cytosolic αSyn would propagate the spread of alpha-synucleinopathy and neuroinflammation by the disruption of autophagy-lysosomal degradation pathway.…”
Section: Discussionsupporting
confidence: 88%
“…αSyn is a major component of Lewy bodies (LB) and Lewy neurites (LN). Most αSyn aggregating in vitro in LB and LN was found in the cytoplasm; however, some αSyn was localized in the nucleus [6][7][8][9]. In previous studies, nuclear αSyn manifested toxic effects on cells [7].…”
Section: Introductionmentioning
confidence: 90%
“…It has been reported that cell‐to‐cell transmission of α ‐Syn aggregates is associated with apoptosis and loss of nuclear membrane integrity; the α ‐Syn aggregates released during cell decomposition can be endocytosed by surrounding cells, causing α ‐Syn to spread to neighboring cells, implying that the speed at which α ‐Syn aggregates are released upon cell death and the fibrotic degree of these released α ‐Syn aggregates determine the extent of α ‐Syn transmission. [ 40 ] These findings prompted us to focus on the effects of α ‐Syn fibrils on cerebral microvascular cell death. As shown in Sections 2.7 and 2.8 , our results provide evidence supporting that Lag3‐dependent α ‐synuclein fibrils endocytosis can induce PAR‐driven cell death in BMVECs.…”
Section: Discussionmentioning
confidence: 99%
“…pS129 facilitates αSyn nuclear import and retention, which disrupts DNA stabilization and repair [ 226 , 227 , 228 ]. Interestingly, inoculation of αSyn pre-formed fibrils (PFF) into the mouse brain leads to the formation of the pS129-αSyn inclusions, subsequent spreading across neurons, and neuronal death [ 229 ]. The above results indicate the potential role of pS129-αSyn and nuclear dysregulation in driving α-synucleinopathies.…”
Section: αSyn-induced Toxicity In Distinct Organellesmentioning
confidence: 99%